2022
DOI: 10.1111/jfpp.16847
|View full text |Cite
|
Sign up to set email alerts
|

The chemistry of flavor formation in meat and meat products in response to different thermal and non‐thermal processing techniques: An overview

Abstract: The flavor is an essential organoleptic trait of meat, affecting its acceptability and delectability towards consumers. Flavor, in the meat, is formed through thermally produced reactions, including vitamin degradation, maillard reaction and lipid oxidation.Such reactions lead to the development of meat flavor with some bloody taste and aroma during cooking. However, adverse effects like discoloration, cooking loss, hard texture, and flavor loss can occur due to conventional cooking. Currently, some novel ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 124 publications
0
2
0
Order By: Relevance
“…glutamates and ribonucleotides that in synchronization with the Maillard reaction develop an idiosyncratic avour, thereby increasing the chances of consumers' acceptability. [144][145][146] The processing challenges of meat analogues have been minimal with the advent of twin-screw extruders, where proper mixing and uniform heat distribution have enabled their reliability in developing high-quality meat analogues with greater acceptance rates.…”
Section: Bottlenecks In the Development Of Vegan Meatmentioning
confidence: 99%
“…glutamates and ribonucleotides that in synchronization with the Maillard reaction develop an idiosyncratic avour, thereby increasing the chances of consumers' acceptability. [144][145][146] The processing challenges of meat analogues have been minimal with the advent of twin-screw extruders, where proper mixing and uniform heat distribution have enabled their reliability in developing high-quality meat analogues with greater acceptance rates.…”
Section: Bottlenecks In the Development Of Vegan Meatmentioning
confidence: 99%
“…Pada umunya setelah proses pengolahan bahan pangan akan terjadi kerusakan lemak yang terkandung didalamnya. Dalam pemanasan, lemak akan terdegradasi (Afzal et al, 2022). Terjadinya penurunan lemak setelah pemanasan disebabkan karena sifat lemak yang tidak tahan panas, selama proses pemanasan lemak mencair bahkan menguap (volatile) menjadi komponen lain TEKNOTAN, Vol.…”
Section: Hasil Uji Proksimatunclassified
“…Our previous study found that Lactiplantibacillus represented the dominant strain in fermented grass carp ( Xiao et al, 2023 ), while combining Flavourzyme and Lactobacillus plantarum ( L. plantarum ) during grass carp fermentation significantly enhanced its safety and physicochemical quality ( Xu, Xiao, Xu, Guo, & Shi, 2022 ). Flavor crucially affects consumer perception ( Afzal et al, 2022 ). However, the exact impact of Flavorzyme and L. plantarum on flavor development during grass carp fermentation remains unclear.…”
Section: Introductionmentioning
confidence: 99%